SOME FACTORS RELATED TO OUTCOME PRONONIC IN PATIENT AFTER HIP HEMIARTHROPLASTY AND INTERNAL FIXING FOR PATIENTS ≥ 60 YEARS OF AGE AFTER INTERTROCHANTERIC CREST FRACTURES AND/ OR FEMORAL NECK FRACTURES (Vietnam Journal of Community Medicine, 2022)
Target: Identifying several factors related to outcome prononic in patient after hip hemiarthroplastyand internal fixing for patients ≥ 60 years of age after intertrochanteric crest fractures and/ or femoralneck fractures after 1, 3 and 6 months.Object and method: The analytical descriptive study for 115 patients ≥ 60 years of age who havebroken intertrochanteric crest and/or femoral neck and treated in Nghe An Hospital for Traumatologyand Orthopaedics by hip hemiarthroplasty and internal fixing.Findings: The death rate of 115 patients after treating intertrochanteric crest fractures and/ or femoralneck fractures is 3.48%. The factors which have the most relations to death include: Age group [OR=3,512(1,538 – 8,019), p < 0,01]; Hypoproteinemia [OR= 2,859(1,001 – 8,166), p < 0,05]; Postoperative delirium [OR= 2,163(1,450 – 5,980), p < 0,01].
Keywords: Hip hemiarthroplasty; internal fixing; Related; death.